2020
DOI: 10.1186/s12903-020-01103-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between periodontal parameters and non-vital pulp in dental clinic patients: a cross-sectional study

Abstract: Background: Endodontic diseases, such as apical periodontitis, communicate with periodontitis and mutually exacerbate them. However, it remains unclear whether pulp condition is a risk factor for periodontal disease. The purpose of this retrospective study was to examine relations between pulp condition and periodontal parameters in Japanese patients who visited a general dental clinic. Methods: Patients who visited a Japanese general dental clinic from 2016 to 2018 and aged 18 to 81 years were analyzed. Perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In the clinical setting, non-vital pulp is a well-known risk factor for tooth extraction [ 17 ]. In our previous study, we reported that non-vital teeth were related to periodontal disease [ 18 ]. In addition, non-vital pulp is a risk factor for dental caries [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the clinical setting, non-vital pulp is a well-known risk factor for tooth extraction [ 17 ]. In our previous study, we reported that non-vital teeth were related to periodontal disease [ 18 ]. In addition, non-vital pulp is a risk factor for dental caries [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we included smokers and individuals with mild periodontitis, which might be associated with a higher risk of developing ALEO because either one or both conditions frequently coexist with AP (Kato et al., 2020; Pinto et al., 2020). Nevertheless, our study participants significantly improved their periapical status.…”
Section: Discussionmentioning
confidence: 99%
“…It is a foregone conclusion that AP is the ultimate outcome of dental caries, and in many instances, AP develops at the expense of periodontal disease. Indeed, periodontitis has been reported as an independent factor for AP ( 44 ) and non-vital pulp ( 45 ). Although the treatments of AP and periodontitis are entirely different, they target the same aim: eradicating the causative microorganisms and the infected and necrotic tissue, hoping to provide an ideal environment for healing.…”
Section: Discussionmentioning
confidence: 99%